Molluscicidal activity of the plant Acacia mangium (Willd.) against the snail Pomaceae canaliculata (Lam.) / Hendry Joseph … [et al.] - Hendry Joseph (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
The Golden Apple Snail (GAS) or Pomacea canaliculata as it is scientifically known, is a major pest of paddy. It can be managed by using cultural techniques, biological control and synthetic molluscicides. While bio-pesticide is an effective and safer alternative, economical mass production can be a constraint. In Sabah, the planting of Acacia mangium is an agroforestry initiative in the paper pulp industry, and efforts to recycle its industrial byproduct are suggested. Therefore this study aims to screen the beneficial phytochemical compounds of Acacia mangium, to test its molluscicidal activity, and to determine the effective dosage that can cause mortality on GAS. Phytochemical screenings of Acacia mangium methanol extract from the leaves, flower, and bark detected the presence of saponin, a class of chemical compound reported to be toxic to snails. The bark was particularly chosen due to its abundant availability as a processing byproduct. The molluscicidal activity was tested using dip bio-assay experiment. The test solution was prepared by mixing ground Acacia mangium bark with distilled water and the concentration was adjusted to 25 mg/ml, 50 mg/ml, 75 mg/ml, and 100 mg/ml respectively. Furcraea selloa var. marginata, a plant that has been reported to be toxic to GAS was used as positive control and prepared with similar concentrations while distilled water was used as negative control. The Acacia mangium aqueous extract recorded 100% snail mortality starting from the concentration of 50 mg/ml within 24 hours, similar to the Furcraea selloa var. marginata aqueous extract. Meanwhile, no mortality was observed in the negative control solution. The lethal concentration (LC50) of Acacia mangium and Furcraea selloa var. marginata was identified at 25 mg/ml and 24 mg/ml respectively. The results from this study have confirmed the molluscicide effectiveness of Acacia mangium on GAS.